Analysis on RF emission of electrical appliances - Alkahtani A.A.; Nordin F.H.; Sharrif Z.A.M.; Bte N.B.; Mustafa A. (IEEE Computer Society, 2023)
With the increased number of electrical appliances in our daily life, Radio Frequency (RF) emission of electrical appliances and its general effects have imposed a great challenge to researchers dealing with human health and power quality of electrical supplies. Even though studying the general effects of the RF emission from electrical appliances is important, it would be beneficial to study the characteristics of the generated signals and how they differ from one appliance to another. Hence, the aim of this paper is to investigate the signal structure and magnitude variation of the RF signals emitted from electrical appliances. Six electrical appliances were tested and their RF emission was recorded consecutively. The emitted signals were captured using an Active-loop antenna with a range of 1 KHz to 30 MHz and a spectrum analyzer of Agilent E4411B model. Experiment results showed that all the tested appliances emit noticeable and unique RF signals when operating. 2012 IEEE.